2021
DOI: 10.3389/fpsyg.2021.733301
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Drivers of Entrepreneurship Education Performance of Medical Students in the Digital Age

Abstract: COVID-19 has made the entire society pay more attention to medical students training. Medicine development is inseparable from the spirit of innovation, focusing on cultivating medical students' innovative awareness and improving entrepreneurship education performance, which has an irreplaceable effect on both the students themselves and the society. This study is based on the ridge regression model to study the driving factors of the entrepreneurship education performance of medical students. Compared with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Compared to the other studies, our findings are consistent with the previous results. Prior research on the performance of medical students' entrepreneurship education revealed that entrepreneurial leadership components in the form of technological competency are the most frequently found in students (Long et al, 2021). Another study in Thailand also confirms the importance of technological skills as hard skills for entrepreneurial leadership among nurses (Udomluck, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Compared to the other studies, our findings are consistent with the previous results. Prior research on the performance of medical students' entrepreneurship education revealed that entrepreneurial leadership components in the form of technological competency are the most frequently found in students (Long et al, 2021). Another study in Thailand also confirms the importance of technological skills as hard skills for entrepreneurial leadership among nurses (Udomluck, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…This construct was measured by excerpting the scale developed and validated by Watson and McGowan (2019) and Long et al (2021) . Students were asked to what extent they agreed with three items referring to entrepreneurship competition, for example, “Entrepreneurship competition projects are easier to land.” The scale ranged from 1 (strongly disagree) to 5 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Five items were extracted on the entrepreneurial practices scale used by Higgins et al (2018) and Long et al (2021) that captured entrepreneurial practice in higher education settings on a 5-point Likert scale (1 = strongly disagree; 5 = strongly agree). One example item is: “Entrepreneurial practice is supported by special entrepreneurial funds.”…”
Section: Methodsmentioning
confidence: 99%
“…Finally, online questionnaires were officially distributed to college students and graduates who had received entrepreneurship education in 31 provinces of China through the liaison personnel of colleges and universities. A total of 187,914 questionnaires were collected, and 17,150 invalid questionnaires, such as short answer time and invalid school names, were excluded, of which 170,764 were valid, accounting for 90.87% [82,83]. According to the research theme, this study screened the data and finally selected 20,134 college students who had started a social entrepreneurship studio as the research sample.…”
Section: Samplementioning
confidence: 99%